(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This study investigates the perceptions of second- and third-year university students regarding the use of YouTube and podcasts as tools for improving English pronunciation. Twenty students aged 18–21 participated in semi-structured interviews. Findings show that learners value these platforms for their authenticity, accessibility, and motivational features. While students reported improved listening comprehension, pronunciation awareness, and speaking confidence, some struggled with fast-paced speech and the absence of structured learning paths. The paper concludes with practical recommendations for integrating digital audio-visual tools into pronunciation pedagogy and suggestions for future research.